Similarities and differences regarding acute anorexia nervosa and semi-starvation: does behavioral thermoregulation play a central role? - Smith, Lucille Lakier (Frontiers in Behavioral Neuroscience, 2023)
Objective: To clarify the association between acute anorexia nervosa (AN) and semi-starvation (SS) by focusing on similarities and differences in physiology, mood, and behavior. Method: A comparison of published literature between these two groups. Results: Both groups show similar hormonal and metabolic changes in response to caloric restriction and extreme weight loss (~25%). Associated changes result in a reduced body temperature (T core-low). Maintenance of body temperature within a specific range is crucial to survival. However, both groups cannot activate autonomic strategies to maintain their T core-low , such as increasing metabolic rate, constricting skin blood vessels, or shivering. Furthermore, T core-low increases the individuals' "coldness sensations" throughout the body, hence the frequent reports from ANs and SSs of "feeling cold." To eliminate these uncomfortable "coldness sensations" and, importantly, to maintain T core-low , ANs, and SSs "select" different thermoregulatory behavioral strategies. It is proposed that the primary differences between AN and SS, based on genetics, now manifest due to the "selection" of different thermo-regulatory behaviors. AN patients (ANs) "select" hyperactive behavior (HyAc), which increases internal metabolic heat and thus assists with maintaining T core-low ; in harmony with hyperactive behavior is a lively mood. Also related to this elevated arousal pattern, ANs experience disrupted sleep. In contrast, SS individuals "select" a passive thermo-behavioral strategy, "shallow torpor," which includes reduced activity, resulting in energy conservation. In addition, this inactivity aids in the retention of generated metabolic heat. Corresponding to this lethargic behavior, SS individuals display a listless mood and increased sleep. Conclusion: Initial similarities between the two are attributable to physiological changes related to extreme weight loss. Differences are most likely attributable to genetically programmed "selection" of alternate thermoregulatory strategies, primarily to maintain T core-low. However, if acute AN is prolonged and evolves into a chronic condition, AN will more closely align with starvation and more precisely reflect SS symptomology.